Seroprevalence of leishmaniasis, toxoplasmosis, and leptospirosis in the domestic fauna of an anthropized environment of the atlantic forest in the city of rio de janeiro - Ornellas, Renato Orsini; de Lima Barbosa Filho, Carlos José; de Albuquerque, Daniela Duarte Alves; Cordeiro, José Luís Passos; Gremião, Isabella Dib Ferreira; Pereira, Sandro Antônio; Langoni, Hélio; dos Santos, Joelene Rosa [UNESP]; Belo, Vinícius Silva; Figueiredo, Fabiano Borges (Universidade Federal do Paraná, 2020)
The Fiocruz Mata Atlantica Campus (CFMA) represents one of the main urban growth fronts in Rio de Janeiro city. The present study evaluates the environment associated with the seroprevalence of canine visceral leishmaniasis (CVL), toxoplasmosis and leptospirosis in dogs and of toxoplasmosis in cats and production poultry belonging to the residents of the CFMA. Blood samples obtained by the census were used to assess frequency of positivity through serological assays. The proportion of seroprevalence of toxoplasmosis, leptospirosis and CVL were respectively 37.2%, 6.2% and 1.2%. The association with the environment had different results depending on the infection. Seroprevalence of leptospirosis was significantly lower (P=0.03) in dogs from anthropized areas (3%), but this was the only region with cases of leishmaniasis. For toxoplasmosis, there was a higher seroprevalence (50%) in rural scenarios. In cats, the seroprevalence of toxoplasmosis was 32.1% and in poultry, it was 18.1%. The seroprevalence in these animals were similar in the studied environments. The results demonstrate the occurrence of Leishmania sp., Toxoplasma gondii and Leptospira spp. in dogs, cats, hens and ducks living in anthropic environments of the Atlantic Forest, in Rio de Janeiro city, being possible to correlate this occurrence between these domestic animal species and the living environment.
Keywords: Domestic animals; Leishmania spp.; Leptospira sp.; Toxoplasma gondii; Zoonoses